RANCANG BANGUN SISTEM INFORMASI PEMINJAMAN BARANG DI FAKULTAS TEKNIK DAN ILMU KOMPUTER UNSIQ BERBASIS WEBSITE - Saifu Rohman (CV Nature Creative Innovation, 2024)
Borrowing goods is the process of providing an inventory of goods to another party that is needed for an event or activity with the applicable conditions. In general, students borrow items from Administration staff by making a loan letter and handing it directly to the Administration staff. However, data collection and reporting is still done manually. This makes it possible for errors in managing goods data or borrower data. To overcome this problem, this research designs and builds a website-based information system for borrowing goods at the Faculty of Engineering and Computer Science, UNSIQ, which makes it easier to manage goods data for administrative staff. The information system for borrowing goods allows students to easily and quickly apply for loans, approve loans, monitor goods and search for status. The system development method used in this design uses the waterfall method or UML (Unified Modeling Language). The result of this design is a website-based information system for borrowing goods using the Codeigniter 4 framework which can simplify the process of borrowing goods.